ANALISIS YURIDIS TERHADAP PERJANJIAN KREDIT TANPA AGUNAN SEBAGAI SALAH SATU ALTERNATIF PENDANAAN UMKM (USAHA MIKRO, KECIL DAN MENENGAH) DI INDONESIA - Ratu Dara, Romana; Nubatonis, Orpa Juliana; Jacob, Yossie M. Y. (Petitum Law Journal, 2025)
This study aims to conduct a legal analysis of unsecured loan agreements (KTA) as an alternative financing option for Micro, Small, and Medium Enterprises (MSMEs) in Indonesia. KTA has become one of the most widely used financing instruments by MSMEs because it does not require physical collateral from borrowers. However, despite providing easier access to financing, there are several challenges in its implementation, particularly related to the risk of non-performing loans and the legal protection for both parties. This research employs a normative legal approach by examining banking regulations governing KTA agreements and the responsibilities of banks in their execution. The analysis focuses on provisions in banking laws that regulate transparency, fair interest rates, and dispute resolution mechanisms. In addition, the study highlights the role of banks in conducting thorough credit risk assessments and the importance of educating MSME borrowers on sound financial management. The findings of this study indicate that KTA can be an effective solution for supporting the growth of MSMEs in Indonesia, provided that the agreements are implemented in accordance with applicable regulations. The conclusions emphasize the importance of enhancing compliance with banking regulations and transparency in providing information to borrowers. Improved consumer protection and credit risk management are also critical steps to ensure the sustainability of KTA as a financing instrument for MSMEs.